Petalophthalmus papilloculatus sp. nov. (Crustacea: Mysida: Petalophthalmidae), a new bathyal suprabenthic mysid from the Galicia Bank (NE Atlantic Ocean) - Vicente, Carlos San; Frutos, Inmaculada; Cartes, Joan E. (Zootaxa, 2014)
A new species of the genus Petalophthalmus (Crustacea: Mysida: Petalophthalmidae) is described, based on specimens collected from the Galicia Bank (northeastern Atlantic Ocean). This species can be distinguished from the other species of the genus Petalophthalmus by the presence of an ocular papilla on its eyes. P. papilloculatus sp. nov. is morphologically close to the cosmopolitan species P. armiger Willemoes-Suhm, 1875, but can be easily distinguished by the presence of an ocular papilla, the longer antennal scales bearing an apical lobe, the unique chitinous ridge on the molar process, the outwards lengthening of the three cuspidate setae on the outer margin of the uropodal exopod and the armature of the telson. This new species lives on fine and very fine sandy bottoms at the bank flanks, between 1536 and 1809 m depths. Probably related to the special biogeographic characteristics of seamounts, the morphological affinity between the new species and P. armiger supports the hypothesis on a common ancestry and recent divergence between both deep sea mysids. An identification key to world species of Petalophthalmus is provided.